Systematic review about 10 interventions in dermatitis : A document from the Latin American Society of Allergy, Asthma, and Immunology - Sánchez, Jorge (2019)
The Latin American Society of Allergy, Asthma, and Immunology (SLAAI) conducted a systematic search in the Medline and LILACS’ database in order to get articles linked to 10 current questions about dermatitis. The assessment of the quality of the evidence and the strength of the recommendations was made through the GRADE system. The completeness and transparency of the recommendations for this clinical guide were assessed with the AGREE Reports Verification Checklist. The final document was shared with physicians, allergists, dermatologists, and pediatricians, and with patients and academic institutions such as universities and medical scientific societies for external assessment. According to the review, clinical scales should be used to measure the severity of the dermatitis, and some interventions such as the use of probiotics may benefit the patient; nevertheless, more studies are required before this management option can be used in the everyday practice. Other interventions such as dietary restrictions and the use of antihistamines seem to be well-founded only in particular cases and they should not be a general recommendation for all patients. This practical guide presents recommendations for the treatment of atopic dermatitis; these recommendations can be helpful for medical staff, patients, and health systems.